Impact of India’s 2019 Corporate Tax Cut Announcement on the Stock Market - Sharma, Chandan (Indian Journal of Finance, 2022)
The paper analyzed the short-term impact of India’s corporate tax cut announcement in 2019 on the Indian stock market. The paper utilized event study methodology to analyze how stocks across industries reacted to the unexpected announcement of the corporate tax cut. The paper found heterogeneity in the abnormal stock returns across industries due to the announcement. Automobile, cement, construction, consumer goods, financial services, and consumer services saw positive abnormal returns due to the announcement. In contrast, power, information technology, and the pharmaceutical industries saw negative abnormal returns. This asymmetry in the stock returns was explained based on companies’ differential corporate tax rates.